Protein for exercise and recovery - Kreider, R. B.; Campbell, B. (The Physician and Sportsmedicine, 2009)
Abstract: Dietary protein is required to promote growth, repair damaged cells and tissue, synthesize hormones, and for a variety of metabolic activities. There are multiple sources of proteins available; however, animal sources of protein contain all essential amino acids and are considered complete sources of protein, whereas plant proteins lack some of the essential amino acids and are therefore classified as incomplete. There is a significant body of evidence to indicate that individuals who are engaged in intense training require more dietary protein than sedentary counterparts (ie, 1.4-2 g/kg/day). For most individuals, this level of protein intake can be obtained from a regular and varied diet. However, recent evidence indicates that ingesting protein and/or amino acids prior to, during, and/or following exercise can enhance recovery, immune function, and growth and maintenance of lean body mass. Consequently, protein and amino acid supplements can serve as a convenient way to ensure a timely and/or adequate intake for athletes. Finally, adequate intake and appropriate timing of protein ingestion has been shown to be beneficial in multiple exercise modes, including endurance, anaerobic, and strength exercise.